Chromatic Light Therapy for Inhibiting Myopia Progression: Human Studies - Swiatczak, Barbara (Klinische Monatsblätter für Augenheilkunde, 2024)
Myopia, a common refractive error, has been associated with various risk factors, but time outdoors has emerged as a significant protective factor against its onset. This association is believed to be mediated by the influence of sunlight on dopamine release, a neurotransmitter crucial for regulating eye growth. Recent research has explored the specific properties of light in order to identify potential interventions for myopia control in children. Low-level red light therapy has gained attention, and has shown promise in inhibiting myopia progression, although there are concerns about safety and rebound effects. Similarly, blue light stimulation aims to upregulate retinal dopamine activity, yet conclusive evidence supporting its efficacy is lacking. Moreover, researchers explored the use of the entire visible light spectrum by digitally imposing longitudinal chromatic aberration to adjust proper eye growth. Preliminary findings suggest that digitally simulated chromatic aberration could potentially serve as a myopia control strategy and highlights the need for further investigation into long-term effects. As research progresses, understanding the efficacy and safety of light-based interventions for myopia control remains crucial for informing clinical practice and optimizing patient outcomes.
Keywords: RLRL; myopia; light therapy; red light